2018
DOI: 10.3889/oamjms.2018.386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Combined Low Energy Laser Application and Micro-Osteoperforations versus the Effect of Application of Each Technique Separately On the Rate of Orthodontic Tooth Movement

Abstract: AIM:The study was conducted to evaluate the effect of combined low energy laser application and Micro-Osteoperforations versus the effect of the application of each technique separately on the rate of orthodontic tooth movement.PATIENTS AND METHODS:Three parallel groups (each group contained 10 patients) were performed; Group A: In which one side was controlled side, and the other side received micro-osteoperforations (MOPs), Group B: In which one side was controlled side, and the other side received low-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(86 citation statements)
references
References 25 publications
2
81
1
2
Order By: Relevance
“…Several factors affect the rate of tooth movement (Abdelhameed and Refai, 2018, Elkattan et al, 2019, Patterson et al, 2016:Makrygiannakis et al, 2018, Jiang et al, 2017, Jahanbakhshi et al, 2016). It is reasonable to assume that the effect of occlusal interferences was minimal in this study as only class II div I malocclusion cases were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors affect the rate of tooth movement (Abdelhameed and Refai, 2018, Elkattan et al, 2019, Patterson et al, 2016:Makrygiannakis et al, 2018, Jiang et al, 2017, Jahanbakhshi et al, 2016). It is reasonable to assume that the effect of occlusal interferences was minimal in this study as only class II div I malocclusion cases were included.…”
Section: Discussionmentioning
confidence: 99%
“…These include increase in force magnitude and type, regional drug applications, vibratory forces, lasers, and light emitting diode, temporary anchorage devices, inciting regional osteopenia to accelerate the remodelling activity and flapless corticotomy procedure. (Addanki et al, 2017, Chung et al, 2015, Hoffmann et al, 2017, Liou et al, 2011, Kundi, 2018, Abdelhameed and Refai, 2018, Alkebsi et al, 2018, Cassetta et al, 2016, Cassetta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There was no standardized timeline for intervention initiation and canine retraction after extraction of the first maxillary premolars. Two studies initiated canine retraction immediately after the extraction of the maxillary first premolars, 31,36 one waited 1 to 2 weeks, 46 two studies reported waiting around 3 months, 35,38 one reported waiting 4 months, 43 two reported waiting 6 months, 39,50 one study did not report the timing of canine retraction, 44 and 10 reported waiting until levelling and aligning were complete and the patient was placed in the working wire to initiate the intervention and OTM 31,32,40‐42,45,47‐49,51 …”
Section: Resultsmentioning
confidence: 99%
“…We conducted three sensitivity analyses: (a) excluding any high risk of bias studies; (b) excluding any studies which were considered clinically as significant outliers (eg a study with increased frequency and number of MOPs 31 ); and (c) excluding a less invasive corticotomy technique (laser‐assisted flapless corticotomy [LAFC]) from the corticotomy group 32 …”
Section: Methodsmentioning
confidence: 99%
“…Multiple MOP procedures were performed in various studies to achieve this continued effect of cytokine release after giving MOPs, which showed a constant influence for a month on average. 3,9,17,31 Cramer et al 3 in their split-mouth animal study, however, demonstrated the application of eight MOPs at a depth of 7 mm on seven mature male beagle dogs in the jaw side randomly selected through computerized random number generation for the allocation of experimental and control sides. Contrary to the significant results in many studies, 14,17,28,29 there was not an increase in tooth movement rates due to MOPs.…”
Section: Micro-osteoperforations: Literature Searchmentioning
confidence: 99%